THE DEFINITIVE GUIDE TO FORTNITE - Berry, Naomi; Dalrymple, Chris ([Edinburgh, Scotland] : Pillar Box Red Publication, 2020)
The world has gone mad for Fortnite with millions of people around the world heading into battle. If you fancy yourself a Fortnite pro-gamer there's no better way to sharpen your skills than with The Definitive Guide to Fortnite. Give yourself the upper hand and learn everything from the basics on gathering, building and surviving, to how to navigate the map and pro survival tips. There's all the tactics, tricks and strategies you need to give you an edge in this popular online game! And if that's not enough there are puzzles, quizzes and games to test your knowledge and sharpen your wit before you proceed into battle.
"100% unofficial" -- Cover.
Keywords: Fortnite Battle Royale (Game) -- Juvenile literature; Video games -- Juvenile literature; Handbooks and manuals